Інформаційні та програмні рішення задачі оптимального розподілу ресурсів на підприємстві з виробництва електроніки - Тарадуда, С. О. (ХНУРЕ, 2023)
In this work, we will consider one of the class problems of operations research. We formulate the requirements for the implementation of the module developed on the basis of the simplex method, which solves the problems of optimal allocation of resources and profit maximization in the production of electronics. We will describe how information and software solutions to the problem affect production, thus proving the relevance of this problem